Immunopathology and Therapeutic Perspectives of Endometriosis: Scientific Gaps and Emerging Advances in Translational Immunotherapy - Meneses do Rêgo, PhD., Amália Cinthia; Araújo-Filho, PhD., Irami (International Journal of Innovative Research in Medical Science, 2025)
Endometriosis is a debilitating inflammatory disease affecting millions of women worldwide. However, its pathogenesis remains incompletely understood and its treatment is suboptimal. Conventional therapies, primarily hormonal suppression and surgical resection, fail to address the underlying immune dysregulation that drives the persistence, recurrence, and resistance of the lesions. Recent advances in immunology have revealed a multifaceted immunopathological landscape characterized by impaired immune surveillance, altered macrophage polarization, dysfunctional regulatory T cell activity, overexpression of immune checkpoints, and chronic failure of inflammatory resolution. These abnormalities create an immune-tolerant microenvironment that allows ectopic endometrial tissue to evade clearance and to establish itself at multiple anatomical sites. Moreover, growing evidence implicates reproductive and gut microbiota as critical modulators of the immune response in endometriosis, adding another layer of complexity to disease progression and therapy. This integrative review critically examines current evidence regarding immune dysfunction in endometriosis and explores promising immunotherapeutic strategies, including checkpoint inhibitors, cytokine modulators, cell-based therapies, and nanotechnology-driven interventions. Key scientific gaps have been identified, such as the lack of clinical trials, inadequate biomarker validation, insufficient exploitation of cutting-edge technologies, and absence of robust frameworks for assessing reproductive safety. Ethical considerations and translational hurdles are also discussed in this review. By bridging fundamental immunopathology with emerging therapeutic innovations, this review highlights the transformative potential of immunotherapy in reshaping the future of endometriosis care within the precision medicine paradigm.